Cinobufagin enhances the protective efficacy of formalin-inactivated Salmonella typhimurium vaccine through Th1 immune response. (October 2016) - Wu, Shuai-Cheng; Yi, Peng-Fei; Guo, Xun; Zhang, Li-Yan; Xu, Dao-Xiu; Fu, Yun-Xing; Cui, Zhen-Qiang; Shen, Hai-Qing; Wei, Xu-Bin; Fu, Ben-Dong
Abstract: Cinobufagin (CBG), one active ingredient isolated from Venenum Bufonis, has been demonstrated to have immunoregulatory effect. The aim of this study was to investigate whether CBG can enhance the protective efficacy of formalin-inactivated Salmonella typhimurium (FIST) in mice. ICR mice were immunized with FIST (10 6  CFU/mouse) alone or mixed with CBG (10, 20, and 40 μg) or alum (200 μg) on day 1 and day 15. Two weeks after the second immunization, serum and spleen were sampled for measuring FIST-specific antibody levels, cytokine levels, and splenocyte proliferation. The results showed that CBG enhanced FIST-specific IgG and IgG2a, the levels of interferon-gamma (IFNγ) and nitric oxide (NO), and the splenocyte proliferation response induced by concanavalin A, lipopolysaccharide, and FIST. In vivo protection studies showed that CBG significantly decreased the bacterial burdens in the spleen and prolonged the survival time of FIST-immunized mice challenged with live Salmonella typhimurium . In vivo IFNγ neutralization led to a significant reduction in FIST-specific IgG2a and IFNγ levels, and in the protective efficacy in CBG/FIST-immunized mice. In conclusion, CBG enhances the protective efficacy of formalin-inactivated Salmonella typhimurium vaccine by promoting the Th1 immune response. Graphical abstract: Highlights: Cinobufagin increased the serum FIST-specific IgG and IgG2a levels in mice. Cinobufagin promoted the IFNγ production and the anti- Salmonella effect. The improved protective effect of FIST by cinobufagin was inhibited by anti-IFNγ mAb. Cinobufagin augmented the Th1 immune response in FIST-immunized mice.